A COMPARATIVE STUDY TO EVALUATE THE CLINICAL OUTCOME OF CONJUNCTIVAL LIMBAL AUTOGRAFT AND AMNIOTIC MEMBRANE TRANSPLANT FOR THE TREATMENT OF PRIMARY PTERYGIUM - Chatterjee, Arkendu; Sahar, Shafaque; Roy, Rupam; Mukhopadhyay, Udayaditya (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to assess the safety and effectiveness of the conjunctival limbal autograft (CLAG) and amniotic membrane transplantation (AMT). Methods: After a full pre-operative assessment 100 patients with primary pterygium attending the ophthalmology outpatient department of a teaching hospital in Eastern India, fulfilling the inclusion and exclusion criteria were selected for our study. The patients were explained the procedure of the study and possible outcomes. They were divided into two groups. Group A: Where 10-0 nylon was to be used for CLAG after pterygium excision. Group B: Where 10-0 nylon was to be used for AMT after pterygium excision. Results: There was marked improvement in vision postoperatively more in the AMT group than CLAG. In the AMT group: 34% had a visual acuity of LogMAR 0.00, 30% had LogMAR 0.12, 12% had LogMAR 0.18, and 24% had LogMAR 0.30 after the surgery. In the CLAG group: 52% had a visual acuity of LogMAR, 20% had LogMAR 0.12, 22% had LogMAR 0.18, and 6% had LogMAR 0.30 after the surgery. Graft and suture-related complications were more in the CLAG group than in the amniotic membrane (AM) graft group. Conclusion: In the present study, The CLAG group was found to be associated with more discomfort, and more post-operative complications than AMT. AM may provide a basement membrane rich in various growth factors and matrix proteins, which promotes epithelial cell migration, adhesion, and differentiation. It is also believed to have anti-inflammatory and antifibrotic effects and exerts anti-scarring effects through the transforming growth factor-β pathway. AMT may be a superior treatment in primary pterygium due to lower recurrence rate, shorter surgical times, and better visual and cosmetic outcomes.